A case study for coupling mechanism of anti-rockburst and pressure relief in gas drainage borehole along seam - Jiang, Junjun; Deng, Zhigang; Zhang, Guanghui; Yang, Shengli (Frontiers in Earth Science, 2024)
After high gas mines coal mining reaches deep, the issue of rockburst has become increasingly prominent.Aiming at solving the problem of rock burst in high gas mines, the coupling mechanism of anti-rockburst and pressure relief in gas drainage boreholes along seam has been explored. The research results indicate that gas drainage boreholes can reduce the stress environment of coal, making the peak stress transfer to deep coal. The pressure relief effect of gas drainage boreholes is slightly weaker than that of large diameter pressure relief boreholes. Moreover, the presence of gas pressure can weaken the mechanical properties of coal. The compressive strength, elastic modulus, cohesion, and internal friction angle of coal all show varying degrees of attenuation with the increase of gas pressure. Besides, a stress analysis was conducted on borehole surrounding rock, and mathematical derivation was also carried out. The expressions for radial stress and circumferential stress of the coal at the boundary of the plastic zone of the borehole surrounding rock, as well as the analytical solution for the boundary of the plastic zone, are obtained. In addition, the gas in pressure relief borehole act on the coal in the pressure relief zone, causing deterioration of the mechanical properties of the coal around the pressure relief boreholes. The expansion range of the radius of the borehole pressure relief zone will increases, and the borehole pressure relief effect will enhance, promoting the formation of coal weakening zones. The above is the coupling mechanism of anti-rockburst and pressure relief in gas drainage boreholes, which has been confirmed by numerical simulation for reliability.Keywords gas coal seam • compound disaster • gas drainage borehole • gas pressure • anti-rockburst and pressure relief • coupling mechanism